KARAKTERISTIK PEMIKIRAN HUKUM ISLAM - Muhammad Harfin Zuhdi (AHKAM : Jurnal Ilmu Syariah, 2014)
Characteristics of Islamic Legal Opinion. Characterising Islamic legal opinion is a way of understanding the Islamic thought which has developed in historical reality. Islam as a divine religion, which has the holy Qur’an in the dynamics of history, experiences a dialectic process of interpretation that is strongly associated with dimensions of space and time. Every Muslim intellectual has an individual perspective in understanding the religion’s doctrine. In this context, there are visible dialectal encounters of discourse in the arena of contestation of Islamic legal opinion with a wide range of variants in understanding Islamic law. Several variants of Islamic legal opinion are revivalist, modernist, neo-revivalist and neo-modernist, or traditional, moderate and liberal. These categories are representive of the struggle of ideas in the Islamic world, including Indonesia.DOI: 10.15408/ajis.v14i2.1276